Problem of Professional Self-Determination of Senior Pupils in Conditions of Modern Labour Market (by Example of Tobolsk) - N. Y. Abysheva; O. N. Gauch (Научный диалог, 2017)
The problem of professional self-determination of graduates of secondary school is considered, which is directly linked with the request of modern society for the training of representatives of working professions. The authors point out the need for an integrated approach to the solution of this problem in the conditions of modernization of school education. The emphasis is made on the study of self-determination as the process of understanding and regulation of life in accordance with moral values. A review of legal documents is made, focusing on the formation of professional competencies that will help the graduate of the primary school to adapt in society when choosing a career. The results of a comparative analysis of the Bank of vacancies of Tobolsk Centre of Employment and the Department of Labour and Employment of the Tyumen Region are presented. The ratio of occupations demanded in the labor market are analysed, as well as career preferences of today’s youth. The conclusions are made by the authors based on the research of the interest of Tobolsk students to certain professions. The study had two stages: at ascertaining step the propensity of the graduate to work in various fields of professional activity was determined, in the control phase professions were identified to which graduates of the schools give the highest preference, and their compliance with the requirements of the modern labour market was established.